Validation of a Likert questionnaire for creative writing and critical thinking in five Spanish universities - Gómez-Caballero, Marta; Soto Vázquez, José; Pérez Parejo, Ramón (Frontiers in Education, 2026)
IntroductionThis study has the overarching objective of designing and validating a Likert-scale questionnaire to gather and analyze data concerning students’ writing skills and critical reasoning in Teacher Training degrees at five Spanish universities.MethodsThe sequence of the research process was as follows: definition of the construct, generation of items, selection of the response format, review by statistics experts, pilot test, psychometric analysis, review and adjustment, sample calculation and request for Bioethics Committee authorization.ResultsThe resulting questionnaire is a four-choice Likert-scale with 31 items in total divided into four factors: Declared Practices, Adherence to Principles, Self-Image as a Writer, and Resources, further broken down into various dimensions.DiscussionFactor analysis and pilot testing confirmed the suitability of the structure. As limitations, in this phase of the research, the surveys are being implemented and the initial data is being collected. The investigative sequence is as follows: definition of the construct, generation of items, selection of the response format, review by statistical experts, pilot test, psychometric analysis, review and adjustment, sample calculation, and Bioethics Committee authorization. A series of subsequent validation tests of the instrument are planned for possible extrapolation to other research contexts.